IMPLICATIONS OF ABC COSTING METHOD - Sánchez Barraza, Bernardo (2013)
Every company to compete successfully in their business, need to know exactly what are their costs of production, because they determine the level of income and measurement profits of the companies. The traditional costing methods are challenged today by stating that not accurately assign costs to products. Faced with this problem, there is the ABC costing method (Activity Based Costing) as a cost allocation method is more realistic and accurate, so in our research, we will carry out a theoretical review of these costing methods. The motivation of this research is that we think the Peruvian industrial sector manufactures products of international quality, but to achieve an appropriate development of this sector, industrial enterprises need to know their exact costs to see if they are competitive in comparison with industrial powers at the global level. Finally, we are confident that this research will generate new knowledge of costs that will be useful to the reader who may have similar problems in any business item.